Enhanced metal exsolution at the non-polar (001) surfaces of multi-faceted epitaxial thin films. (1st January 2023) - Weber, Moritz L; Kindelmann, Moritz; Wessel, Egbert; Sarantopoulos, Alexandros; Menzler, Norbert H; Dittmann, Regina; Waser, Rainer; Guillon, Olivier; Lenser, Christian; Gunkel, Felix
Abstract: Metal exsolution is a dynamic process driven under a reducing atmosphere and at elevated temperatures that results in the self-assembly of nanoparticles at the surface of complex perovskite catalysts. The nanoparticle characteristics of metal exsolution catalysts can be subject to considerable inhomogeneity, and the anisotropic surface properties of ceramic oxides have been identified to have a major influence on the exsolution behavior. We systematically reveal the orientation-dependent anisotropy of the exsolution behavior of Ni in SrTi0.9 Nb0.05 Ni0.05 O3−δ using multi-faceted epitaxial thin films that represent a material system with properties in between functional ceramics and single-crystalline perovskite thin film model systems. Using an approach of combined orientation mapping and surface imaging we study the exsolution behavior with particular focus on the initial exsolution response, i.e. after short annealing times. We find orientation-specific variations in the surface morphology of the thin film facets. In the as-prepared state, surface reconstructions cause the formation of patterned surface structures for all thin film facets apart from (001) surfaces, which exhibit a plain surface morphology as well as an enhanced exsolution response. Surface reconstructions and their inherent energy landscape may hence cause an additional energy barrier for the exsolution reaction that results in orientation-dependent differences in the exsolution kinetics.